The Cinema of Federico Fellini - Bondanella, Peter (Princeton University Press, 1992)
This major artistic biography of Federico Fellini shows how his exuberant imagination has been shaped by popular culture, literature, and his encounter with the ideas of Carl Jung, especially Jungian dream interpretation. Covering Fellini's entire career, the book links his mature accomplishments to his first employment as a cartoonist, gagman, and sketch-artist during the Fascist era and his development as a leading neorealist scriptwriter. Peter Bondanella thoroughly explores key Fellinian themes to reveal the director's growth not only as an artistic master of the visual image but also as an astute interpreter of culture and politics. Throughout the book Bondanella draws on a new archive of several dozen manuscripts, obtained from Fellini and his scriptwriters. These previously unexamined documents allow a comprehensive treatment of Fellini's important part in the rise of Italian neorealism and the even more decisive role that he played in the evolution of Italian cinema beyond neorealism in the 1950s. By probing Fellini's recurring themes, Bondanella reinterprets the visual qualities of the director's body of work - and also discloses in the films a critical and intellectual vitality often hidden by Fellini's reputation as a storyteller and entertainer. After the first two chapters dealing with Fellini's precinematic career, the book covers all the films to date in analytical chapters arrangedby topic: Fellini and his growth beyond his neorealist apprenticeship, dreams and metacinema, literature and cinema, Fellini and politics, Fellini and the image of women, and La voce della luna and the cinema of poetry.